Implementation of a Deep Learning Approach through Problem-Based Learning in Science Learning at Zahira Private Elementary School - Jihan Fauziah; Sapri (Indonesian Technology and Education Journal, 2026)
This study aims to describe the implementation of a deep learning approach in science learning at Zahira Private Elementary School through the Problem-Based Learning (PBL) strategy. This study employed a qualitative approach with a descriptive method. The participants of this study consisted of 7 IPAS teachers, 1 school principal, and 35 fifth-grade students at Zahira Private Elementary School. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of the deep learning approach was carried out through three main stages: planning, implementation, and evaluation. In the planning stage, teachers developed lesson plans or teaching modules incorporating contextual problems related to ecosystems and encouraging higher-order thinking skills. In the implementation stage, learning activities involved problem-solving and direct observation outside the classroom, enabling students to relate scientific concepts to real-life experiences. Teachers also incorporated elements of mindful, meaningful, and joyful learning through open-ended questions, contextual learning experiences, and educational games. In the evaluation stage, assessment was conducted formatively, emphasizing learning processes and continuous feedback. The study found that students showed increased activeness, engagement, and participation during the learning process. However, several challenges were identified, including teacher readiness and varying levels of student engagement. Therefore, continuous support is needed to optimize the implementation of the deep learning approach in classroom practice.